Equal Antiplatelet Effects of Aspirin 50 or 324 mg/Day in Patients After Acute Myocardial Infarction - De Caterina, R; Giannessi, D; Boem, A; Bernini, W; Battaglia, D; Michelassi, C; Dell’Amico, F; L’Abbate, A; Patrignani, P; Patrono, C (Thrombosis and Haemostasis, 1985)
This study explores the effects on some hematological parameters of a low-dose aspirin regimen (50 mg/day) versus a conventional aspirin treatment with reported antithrombotic efficacy (324 mg/day), in patients with acute myocardial infarction. Fifteen patients were randomized into 3 equal groups receiving 50 mg or 324 mg aspirin or placebo, daily for 21 days. Compared with placebo, bleeding time was significantly and similarly prolonged with both aspirin doses (+ 71 ± 22% and + 69 ± 20%, mean ± S.D.). Aspirin 50 mg/day suppressed arachidonate-induced platelet aggregation and secondary phase aggregation after ADP and adrenaline. Collagen aggregation was inhibited by 44 ± 15%. In no case were differences in the antiplatelet effects of the two doses observed. The effects of 50 mg/day persisted without attenuation during the observation period. Platelet thromboxane B2 generation during arachidonate-induced aggregation was inhibited by 95 ± 2 and 99 ± 1% compared to placebo group after 50 and 324 mg/day, respectively (P between doses <0.05). No change was observed with any treatment in coagulation time, prothrombin time or plasma thromboplastin time. Thus, in patients with acute myocardial infarction, the antiplatelet effects of aspirin 50 mg/day are stable over time and superimposable on those of 324 mg/day. The antithrombotic efficacy of aspirin 50 mg/day remains to be tested clinically.
Keywords: Aspirin; Myocardial infarction; Thromboxane; Prostacyclin